Hubungan Antara Status Gizi dengan Kejadian Malaria di Puskesmas Senggo - Maryam Jamaluddin (Jurnal Siti Rufaidah, 2025)
Based on global reports, there were 247 million malaria cases in 2021, increasing from 245 million cases in 2020. In Indonesia, the Ministry of Health recorded 254,055 malaria cases in 2020. Three provinces—Maluku, Papua, and West Papua—have not yet achieved malaria elimination. Malaria is an acute febrile disease caused by the Plasmodium parasite, transmitted to humans through bites of infected female Anopheles mosquitoes. It remains a significant public health problem due to its impact on morbidity, mortality, and productivity in endemic areas. This study aimed to examine the relationship between nutritional status and malaria incidence among patients in the working area of Senggo Health Center. An analytical descriptive approach with a cross-sectional study design was applied. The study population included all malaria patients examined at Senggo Health Center, Citak Mitak District, Papua, totaling 559 patients in February. A sample of 243 respondents was selected using the Table for Determining Needed Size of a Random Sample. Results showed that most respondents suffered from mild malaria, and the majority had normal nutritional status. Statistical analysis indicated a significant relationship between nutritional status and malaria incidence in the Senggo Health Center area. Respondents with poor nutritional status were more likely to experience malaria with severe symptoms compared to those with normal or good nutritional status. These findings highlight the critical role of nutrition in malaria prevention. Nutritional interventions should be integrated with vector control measures and public health education to reduce malaria incidence and improve community health. Improving nutritional status, particularly in endemic regions, is essential for enhancing immunity, reducing disease severity, and supporting overall malaria control efforts. Nutritional status significantly influences malaria incidence. Public health programs targeting nutritional improvement are necessary to complement existing malaria control strategies, reduce case numbers, and promote better health outcomes in endemic areas.